MUSCULOSKELETAL COMPLAINTS IN MOTORCYCLE TAXI PILOTS - França, Deyse Xavier de Sousa; Bakke, Hanne Alves (Journal of Health Care, 2015)
quickness and access to remote areas. But few studies analyze the postures adopted in this profession that,when inadequate, can cause disorders that unable one from developing his activities. Objectives: To raisethe musculoskeletal symptoms and their pain degree; to study the relationship between musculoskeletalsymptoms and factors related to work and conduct a biomechanics analysis in postures adopted in themotorcycle taxi pilot activity. Material and methods: The study was conducted with 20 motorcycle taxipilots from a small city in Paraíba, whom were chosen randomly. A semi-structured questionnaire wasused in the research, as well as the Corlett’s corporal diagram and the REBA ergonomic software analysis.The relationship between the musculoskeletal symptoms and the variables: age, service time and workhours was analyzed by the student t test. Results: This profession involves young individuals with lowacademic levels, that submit themselves to long working hours. Pain was referred by 10 pilots with greaterincidence among the individuals, with 20 to 30 years of age. The body part most compromised was the back. Working hours were significantly higher among the pilots that referred pain (p=0.01). Conclusion:Musculoskeletal symptoms are compatible with sitting work postures, and the biomechanical risk whileconducting the vehicle is medium, demanding changes. Working hours can be a risk factor for the developmentof the disorders in these workers.